Biofuel pulse combustion characteristics - Abd. Wahid, Mazlan (Faculty of Mechanical Engineering, 2009)
The phenomenon of pulse combustion of hydrocarbon-oxygen mixtures was investigated experimentally. An experimental rig that consists of a stainless steel tube with inner diameter of 100mm, complete with data acquisition system, ignition control unit and filling system was built in order to measure the characteristics of pulse combustion such as, pressure, velocity and cell width. Two types of hydrocarbon fuels were used in this investigation, which were propane and natural gas with 92.7% methane. Synthetic biogas was produced by mixing 65% natural gas with 35% carbon dioxide. Results showed that natural gas and biogas are not sensitive to detonation propagation compared to propane. The oxygen concentration in the oxidizer mixture was diluted with nitrogen gas at various percentage of dilution. It was found that in smooth inner wall tube, combustion wave propagate as a detonation wave if the percent of dilution gas is not more than approximately 35%. Combustion wave may accelerate and transit into detonation wave if it propagates in a very long channel. In order to accelerate the combustion wave into detonation wave within 0.5m of the tube, array of obstacles with identical lockage ratio was placed inside the tube near to the ignition source. It was confirmed that the obstacle could enhance the transition process within the given length.